Safety and efficacy of dual versus triple antithrombotic therapy in Patients with atrial fibrillation undergoing percutaneous coronary intervention: a meta-analysis - Moustafa, Abdelmoniem; Khan, Mohammad; Saud, Marei; Abdalla, Alsamman Mohd; Amer, Baig; Muhammad, Saad (Avicenna Journal of Medicine, 2020)
Background: Patients with atrial fibrillation undergoing percutaneous coronary intervention have indications for oral anticoagulation and dual antiplatelet therapy (DAPT) with aspirin and a P2Y12 receptor inhibitor. The concurrent use of all three agents, termed triple oral antithrombotic therapy (TAT), increases the risk of bleeding. A number of prospective trials showed that the omission of aspirin mitigates the risk of bleeding without affecting major adverse cardiovascular event (MACE). Materials and Methods: The databases of PubMed, Embase, and Cochrane Central databases were searched from inception to October 2019. Relevant randomized control trials comparing dual antithrombotic therapy (DAT) versus TAT were identified and a metanalysis was performed using random-effect model. The safety endpoints of interest were thrombolysis in myocardial infarction criteria (TIMI) major and minor bleeding, TIMI major bleeding, and intracranial bleeding. The efficacy endpoints of interest were MACE and individual components of MACE. Results: Six trials with 11,722 patients were included. For safety endpoint, DAT was associated with significantly lower incidence of TIMI major and minor bleeding [RR: 0.58, 95% CI 0.44–0.77, P = 0.0001], TIMI major bleeding [RR: 0.55, 95% CI 0.42–0.73, P < 0.0001] as well as intracranial bleeding [RR: 0.35, 95% CI 0.16–0.73, P = 0.006] compared with TAT. No significant difference was observed for MACE [RR: 0.96 (0.79–1.17) P = 0.71] or any of the individual components of MACE between the two groups. Conclusion: Omission of aspirin from TAT in patients with Atrial Fibrillation (AF) after percutaneous coronary intervention is associated with lower risk of bleeding without compromising the efficacy in terms of mortality and cardiovascular thrombotic events.
Keywords: Atrial fibrillation; CAD; coronary artery disease; dual antithrombotic therapy; stent; triple antithrombotic therapy